PENGARUH MEDIA PEMBELAJARAN KOMIK TERHADAP KETERAMPILAN BERCERITA BAHASA INDONESIA SISWA KELAS III JATICEMPAKA VI BEKASI - Nanda Saputra; Septi Fitri Meilana (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to determine the effect of comic learning media on Indonesian language storytelling skills of 3th grade students. This research is a quantitative study using the Quasy Experimental type of research method with the type of The Nonequivalent Posttest-Only Control Group Design. The population of this study included all 3th grade students of SDN Jaticempaka VI in the second semester of the 2020/2021 school year. The sample studied was 32 students from class III A and class III B. The sampling technique used a saturated sampling model. The research instrument was a description of 6 questions. The data analysis technique consists of two stages of data distribution on the results of students' storytelling skills and hypothesis testing includes the t-test by seeing the differences in storytelling skills in the experimental class and the control class with a significant level of 0.05%. Based on the results of the post-test, it was found that the average score of students' storytelling skills after being taught using comic media (experimental class) was higher than the average score for storytelling skills of students who did not use comic media (control class). The average post-test score of the experimental class was 96 and the control class 82.